H.G.R. King and the Scott Polar Research Institute - Martin, Constance (ARCTIC, 1992)
[This profile celebrates the accomplishments of the Scott Polar Research Institute and its former head librarian Harry King.] . King's career and his relationship with the library of the Scott Polar Research Institute and with the hundreds of polar scholars, scientists and enthusiasts from all over the world are probably best summed up by the late Alan Cooke, who in a letter shortly before his death in 1989, wrote: "I know virtually nothing of his [Harry King's] biographical details, although I was his assistant librarian from 1967-1975 and, of course, I already knew him well when I was a graduate student in the SPRI, 1963-1965. I think of him as knowledgeable, patient, humorous, full of good will. He is the best kind of specialist librarian, thoroughly familiar with the literature in his care. His long experience of aiding scholars in every field of polar study gave him an unrivalled familiarity with the whole range of polar literature, and his book on Antarctica is abundant evidence of his special interest in that region." .